(untitled) (Fiep Bulletin - online, 2015)
Diverse authors (GODTSFRIEDTet al., 2010;MONTIELetal., 2014) have discussed the relationship between mental preparation and sports performance, and how often the imagination produced, arranged and directed to a particular task can influence the way practical realization of this same task. The objective of this study was to examine whether motor imagery alters the performance of looting beneath young beginners in volleyball practice. To this end, the sample consisted of 21 young people, who were divided into two groups: an experimental group of 10 young with an average age of 15.8 years (SD = 1.23) and control group of 11 young people the average age of 16.6 years (SD = 1.22). For statistical analysis we used SPSS 22 software. The Normality Test denominated Shapiro-Wilk was performed to evaluate the distribution of the sample data and the Student t test to calculate differences intergroups and between groups considered for the significance level of p <0 01. The results showed no significant difference between groups in pre-test demonstrated the technical similarity between the groups. Comparing the two groups before and after the program of motor imagery was found a significant difference in the experimental group showed an increase in the accuracy of the loot underneath, unlike the control group showed a significant decrease in the accuracy of looting by demonstrating that low, probably the lack practicing during the experiment causes the acquired skill does not have enough to be used with the same performance consistency. It was concluded that motor imagery positively influence the accuracy of the loot underneath in young beginner in volleyball.